Massive scalar field evolution in de Sitter - Markkanen,T; Rajantie,A (Journal of High Energy Physics, 2017)
The behaviour of a massive, non-interacting and non-minimally coupledquantised scalar field in an expanding de Sitter background is investigated bysolving the field evolution for an arbitrary initial state. In this approachthere is no need to choose a vacuum in order to provide a definition forparticle states. We conclude that the expanding de Sitter space is a stableequilibrium configuration under small perturbations of the initial conditions.Depending on the initial state, the energy density can approach its asymptoticvalue from above or below, the latter of which implies a violation of the weakenergy condition. The backreaction of the quantum corrections can thereforelead to a phase of super-acceleration also in the non-interacting massive case.